Synthesis and Characterisation of Polyester Resin Matrix Composites Reinforced with Pineapple Leaf Micro Particles - Durowaye, Stephen; Sekunowo, Olatunde; Kuforiji, Catherine; Lawal, Ganiyu; Okon, Jacob (Journal of the Institute of Engineering, 2019)
Reinforcement of polymers with particles to enhance their mechanical properties for various applications cannot be over emphasized. Hence, the microstructure and mechanical behaviour of polyester resin matrix composites reinforced with pineapple leaf particles was studied in order to develop an engineering material for industrial applications. Pineapple leaf particles treated and untreated with NaOH were separately blended with unsaturated polyester resin. 1 g of catalyst and 0.5 g of accelerator were added to the mixture to achieve a homogeneous interfacial interaction. The composites were made by mould casting and their microstructure and mechanical properties were evaluated. The NaOH treated pineapple leaf particles reinforced composite exhibited the highest tensile strength of 98.73 MPa at 15 wt. % and impact energy of 20.73 J at 20 wt. %. Microstructure showed a fairly uniform distribution of the pineapple leaf particles in the polyester resin matrix coupled with the strong interfacial bonding of the filler and matrix as the major factors responsible for the enhancement of the tensile strength and impact energy of the composites.